Comparing Surgical Interventions for Recurrent Lumbar Disc Herniation: A Literature Review: Recurrent Disc - ALSHARAF, Yusuf; ALBAQALI, MOHAMED ABDULLA; Saloom, Fareed; Alqallaf, Abdulla hasan; Sayyad, Dr. Yakub (International Journal of Innovative Research in Medical Science, 2023)
The recurrence of lumbar disc herniation (LDH) is a common complication that can occur after primary discectomy. Various factors contribute to the recurrence of LDH, including patient-related, surgical, and biomechanical factors. Despite attempts to determine the best surgical techniques and patient selection criteria, there is inconsistent evidence that some factors increase the likelihood of recurrence. Repeat discectomy has been shown to be a safe and effective surgical option for recurrent LDH cases that do not respond to non-operative management. However, selecting the most suitable surgical intervention, such as endoscopic or conventional discectomy with or without instrumented fusion, can be difficult. Factors such as presenting symptoms, previous surgeries or re-herniations, radiographic instability, sagittal or coronal deformity, and surgeon experience should all be considered when making this decision. Further comparative clinical investigations are needed to establish the best surgical method.